The Role of Bone-Derived Exosomes in Regulating Skeletal Metabolism and Extraosseous Diseases - Lyu, Huili; Xiao, Ye; Guo, Qi; Huang, Yan; Luo, Xianghang (Frontiers in Cell and Developmental Biology, 2020)
Bone-derived exosomes are naturally existing nano-sized extracellular vesicles secreted by various cells, such as bone marrow stromal cells, osteoclasts, osteoblasts, and osteocytes, containing multifarious proteins, lipids, and nucleic acids. Accumulating evidence indicates that bone-derived exosomes are involved in the regulation of skeletal metabolism and extraosseous diseases through modulating intercellular communication and the transfer of materials. Following the development of research, we found that exosomes can be considered as a potential candidate as a drug delivery carrier thanks to its ability to transport molecules into targeted cells with high stability, safety, and efficiency. This review aims to discuss the emerging role of bone-derived exosomes in skeletal metabolism and extraosseous diseases as well as their potential role as candidate biomarkers or for developing new therapeutic strategies.